2017
DOI: 10.1371/journal.pone.0185088
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phosphatidylinositol 3-kinase/AKT/snail signaling pathway contributes to epithelial-mesenchymal transition-induced multi-drug resistance to sorafenib in hepatocellular carcinoma cells

Abstract: Sorafenib, an orally available kinase inhibitor, is the standard first-line systemic drug for advanced hepatocellular carcinoma (HCC), and it exerts potent inhibitory activity against epithelial–mesenchymal transition (EMT) and multidrug resistance (MDR) by inhibiting mitogen-activated protein kinase (MAPK) signaling in HCC. However, after long-term exposure to sorafenib, HCC cells exhibit EMT and resistance to sorafenib. The activation of AKT by sorafenib is thought to be responsible for the development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 39 publications
7
102
0
1
Order By: Relevance
“…Multiple studies have reported that the activation of the PI3K/Akt signaling pathway induces chemoresistance in HCC cells (18)(19)(20). Meanwhile, the MAPK signaling pathway is a major target of sorafenib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that the activation of the PI3K/Akt signaling pathway induces chemoresistance in HCC cells (18)(19)(20). Meanwhile, the MAPK signaling pathway is a major target of sorafenib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…HEK-293T1 cells were seeded in a medium depleted of biotin 24 h before transfection with 10 µg TOM20-mVenus-BirA plasmid per 100 mm plate and grown for another 24 h in biotin-depleted medium before harvest. For siRNA treatments, cells were grown to 50% confluence in biotin-containing media and transfected with siRNA against human Tom70 (Dharmacon M02124301) , human CLUH (Invitrogen 1299003) (Gao et al, 2014) or control irrelevant siRNA (Sense 5 -UUCUCCGAACGUGUCACGU-3 ) (Dong et al, 2017) in a final concentration of 100 nM. At this stage, growth was shifted to a biotin-depleted medium.…”
Section: Biotin Induction and Ribosomes Isolationmentioning
confidence: 99%
“…To establish potential translational relevance of our findings, we surveyed previous studies of molecular mechanisms of sorafenib resistance in human tumors. We found that indeed the InsR/IGF (26,27), EGFR (28,29), Akt (30,31), Src kinases (32), and multiple RTK's (29) were all pathways contributing to sorafenib resistance in human cancer cells. In our Drosophila studies restraining these pathways in normal and transformed cells, either genetically or pharmacologically, correlated with increased sorafenib efficacy ( Fig.…”
Section: Drug Combinations Restrained Hyperactivation Of Cellular Promentioning
confidence: 82%